Cortical Auditory Evoked Potentials in Children with Auditory Neuropathy/Dys-Synchrony - Emami, Seyede Farank (Indian J Otolaryngol Head Neck Surg, 2018)
Auditory neuropathy/spectrum disorder (ANSD), also referred to as auditory neuropathy/dys-synchrony (AN/AD) is a recently described form of hearing impairment. Many studies have shown that changing the pattern of afferent input to the cortex significantly affects cortical organization and there is little studies about cortical neuromaturation and plasticity in children with ANSD. Study of P1 component of cortical auditory evoked potentials (CAEPs) in children with ANSD. This survey was descriptive cross-sectional. During that 97 hearing impairment children were under hearing screening tests. Of these, 14 selected subjects (ear = 28) diagnosed with ANSD (an average age of 8.5 years) and evaluated by P1 component of CAEPs. Based on latency results of p1 wave, the ears of the subjects fell into two seperate groups: Control (normal: n = 10) and case {total: n = 18 (delayed: n = 12) + (absent: n = 6)}. The averages of mean latency of P1 components of the case group in the right and the left ears compared to the control group had significant differences (p < 0.05). Abnormal latency of p1 component in ANSD children shows the possibility of different scales of disturbances in cortical auditory maturation and grow.